A Process Of Implementing Zigbee Protocol With Machine Learning Algorithm For Greenhouse Set-Up - et. al., E Mercy Beulah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The greenhouse effect is considered as the natural process used for warming the earth's surface. When energy from the sun reaches the earth's atmosphere, some of its power will be reflected in space, and the remaining energy will be absorbed. The greenhouse gases will redirect it. One of the main advantages of greenhouse gas is that it has a protective benefit in agro-system compared to open-air cultivation and unprotected cultivation. But monitoring of greenhouse in agricultural and other environments seems to be a difficult task in the present time. Because it will be used for regulated environmental aspects such as temperature, humidity, light, gas, pH-level, and soil, Green House operation has been incorporated with IoT protocols in this research paper. The Zigbee 3.0 protocol helps in increasing the effectiveness of monitoring the greenhouse system. This paper aims to present a novel wireless Internet of Things network-based ZigBee technology for monitoring and controlling greenhouse climate. Because they are some significant parameter need to be monitored in the Greenhouse system, this protocol starts monitoring the Internet of Things connected to the wireless Internet of Things network.Along with protocol, In this research, a Cloud and Internet of Internet of Things-based algorithms such as the Reinforcement Learning- (RL), RF(Random Forest), and EAD(enhanced AdaBoost has been implemented to monitor the GH parameter. The performance evolution of the Algorithm is compared to show which Algorithm is capable of monitoring the GH parameter. This research aims to produce a real-time module for monitoring and controlling the parameter because it can measure the Execution time, memory, energy consumption, and overall accuracy.